Comparative proteomics and metabolomics reveals distinct host protein quality control and metabolic signatures during recombinant IL1-His and IL15-His expression in Nicotiana benthamiana - Alina Savinova; Theerakarn Srisangsung; Pipob Suwanchaikasem; Waranyoo Phoolcharoen (PLoS ONE, 2026)
Agrobacterium-mediated transient expression in Nicotiana benthamiana is widely used for recombinant biopharmaceutical production. To investigate the host plant response upon human cytokine production with contrast accumulation, we expressed codon optimized human IL1 beta, serving as a high expression benchmark with a yield of approximately 80 μg/g leaf fresh weight, and IL15 with undetected signal on western blot, representing protein with low level of accumulation, using the geminiviral vector system. A combined proteomics and metabolomics technique was applied to elucidate underlying cellular mechanisms. Quantitative proteomics revealed that IL1-His was robustly detected (9 unique peptides, 83% coverage), whereas no IL15-His–derived peptides were identified. Based on pathway analysis, the expression of IL15-His induced chaperone expression, with downregulation of photosynthetic and primary metabolism pathways. Additionally, metabolomic pathway analysis revealed that IL1-His preferentially drives the branched chain amino acid biosynthesis, but IL15-His shifts metabolism towards phenylpropanoid biosynthesis routes. These findings underscore that the characteristics of the target protein and its interaction with the host's physiology could influence the yield of the recombinant protein production in plants.